Enhancing photocatalysis through annealing: Unveiling the role of physical properties in photocatalytic behavior - Tiss, Belgacem; Zayoud, Wafa; Sekrafi, Houssem Eddine; Bouguila, Noureddine; Cristea, Daniel; Croitoru, Cătălin; Velicu, Ioana Laura; Tiron, Vasile; Prepeliță, Petronela; Crăciun, Valentin; Moura, Cacilda; Cunha, Luis (Elsevier BV, 2024)
Using spray pyrolysis, silver-doped In2S3 thin films were deposited on pre-heated glass substrates, with varying doping concentrations. Subsequently, these films underwent vacuum annealing at 400 °C for a duration of 2 h. A comprehensive study of their structural, morphological, and optical properties was conducted, revealing homogeneous, compact, crack-free films with polycrystalline tetragonal-phase of In2S3. Among the set of the analyzed films the best parameter values, including crystallite size, dislocation density, micro-strain, grain size, and root mean square (RMS) roughness, were achieved when maintaining a Silver-to-indium (|Ag|/|In|) ratio of 4 % in the precursors for both as-deposited and annealed samples. The annealing process had a discernible impact on the grain size distribution, resulting in a significant increase in crystallite and grain size, along with RMS roughness, for most doped films. The optical analysis of these films unveiled their transparency in the visible and near-infrared regions, coupled with substantial absorption in the UV region. Higher Ag concentration in the as-deposited films led to an increased band gap energy in the annealed samples. The roughness peaked at |Ag|/|In| = 4 %, resulting in a noteworthy enhancement of photocatalytic activity, achieving 95 % photodegradation of a methylene blue aqueous solution. This underscores the critical role of surface properties in determining performance. Future research intends to explore other applications for these thin films, including potential usage in gas sensors, capitalizing these films' promising characteristics.
Keywords: Spray pyrolysis; Annealing; In2S3:Ag films; Physical properties; Photocatalytic activity